Pengaruh Risiko Spekulatif, Risiko Operasional, Dan Volume Penjualan Terhadap Kinerja Keuangan PT. Prima Multi Mineral - Robby Gunawan; Meina Wulansari Yusniar; Asrid Juniar (Universitas Lambung Mangkurat, 2019)
This study aimed to determine the influence of speculative risk (X1), operational risks (X2), and the volume of sales (X3) simultaneously and partially toward the Company's financial performance: profit margin (Y1) and return on assets (Y2). The type of this study was causality research. This study used saturated sampling such as historical data of sales volume, the Newcastle index, and the record of operational risks that occurred during the period of April 2011 until December 2013. The correlation between the variables X1, X2, X3 toward Y1 and Y2 were dertermined using multiple linear regression correlation techniques and to determine the level of significance using hypothesis test such as coefficient determination test, F test and t test which processed by SPSS program series 21. The results of this study concluded that three independent variables affect toward the dependent variable simultaneously and partially there were negative influence of operational risk (X2) toward profit margin (Y1) and ROA (Y2), while sales volume (X3) effect positively towards profit margin (Y1) and ROA (Y2).